Osmotic dehydration and convective drying of kiwifruit (Actinidia deliciosa) – The influence of ultrasound on process kinetics and product quality - Kroehnke, Joanna (Ultrason Sonochem, 2020)
The aim of this study was to assess the impact of ultrasound on two subsequent processes – initial osmotic dehydration and convective drying of kiwifruit (Actinidia deliciosa). The effect of ultrasound (at a frequency of 25 kHz) was assessed both in terms of process kinetics and product quality. During the study, three different osmotic agents were used – erythritol, sorbitol, and sucrose – in an aqueous solution at a concentration of 50% (w/w). The essential kinetic parameters were analyzed – water loss and increase of dry matter during osmotic dehydration, and evolution of moisture content and temperature of samples during convective drying (drying curves). Product quality was assessed on the basis of color, water activity, and content of relevant bioactive components – polyphenols and carotenoids. It was found that the application of ultrasound during osmotic dehydration resulted in higher water loss and solid gain. This surely results from the phenomena occurring during the propagation of the elastic waves in the liquid medium (mainly related to cavitation) and enhancement of the mass transfer. The use of ultrasound during convective drying also had a positive effect on the kinetics of this process. In most cases, during the ultrasonically assisted drying operations, a significant increase in drying rate was observed, leading to a reduction in drying time. This may be due to the intensification of both heat and mass transfer as a result of the mechanical and thermal effects of ultrasound. The assessment of product quality showed that the use of sugar alcohols was a good alternative to sucrose, and ultrasound-assisted convective drying increased the retention of valuable carotenoids and polyphenols. Moreover, in all dried kiwifruit slices, water activity was below 0.6, which can guarantee the microbiological stability of the tested samples.